Outcome and prognostic factors in cerebellar glioblastoma multiforme in adults: A retrospective study from the rare cancer network - (:unkn) unknown (ELSEVIER SCIENCE INC, 2006)
Purpose: The aim of this study was to assess the outcome in patients with cerebellar glioblastoma (GBM) treated in 15 institutions of the Rare Cancer Network. Methods and Materials: Data from a series of 45 adult patients with cerebellar GBM were collected in a retrospective multicenter study. Median age was 50.3 years. Brainstem invasion was observed in 9 (20%) patients. Radiotherapy (RT) was administered to 36 patients (with concomitant chemotherapy, 7 patients). Adjuvant chemotherapy after RT was administered in 8 patients. Median RT dose was 59.4 Gy. Median follow-up was 7.2 months (range, 3.4-39.0). Results: The 1-year and 2-year actuarial overall survival rate was 37.8% and 14.7%, respectively, and was significantly influenced by salvage treatment (p = 0.048), tumor volume (p = 0.044), extent of neurosurgical resection (p = 0.019), brainstem invasion (p = 0.0013), additional treatment after surgery (p < 0.001), and completion of the initial treatment (p < 0.001) on univariate analysis. All patients experienced local progression: 8 and 22 had progression with and without a distant failure, respectively. The 1- and 2-year actuarial progression free survival was 25% and 10.7%, respectively, and was significantly influenced by brainstem invasion (p = 0.002), additional treatment after surgery (p = 0.0016), and completion of the initial treatment (p < 0.001). On multivariate analysis, survival was negatively influenced by the extent of surgery (p = 0.03) and brainstem invasion (p = 0.02). Conclusions: In this multicenter retrospective study, the observed pattern of failure was local in all cases, but approximately 1 patient of 4 presented with an extracerebellar component. Brainstem invasion was observed in a substantial number of patients and was an adverse prognostic factor. (c) 2006 Elsevier Inc.
Keywords: cerebellar glioblastoma; malignant glioma; posterior fossa tumors; radiotherapy; chemotherapy; BRAIN-STEM GLIOMAS; PHASE-II; TEMOZOLOMIDE; RADIOTHERAPY; RADIATION; INFRATENTORIAL; ASTROCYTOMAS; IRRADIATION; CHILDREN; TRIAL